Recent advances in nanocellulose-based different biomaterials: types, properties, and emerging applications - Muhammad Yasir Khalid (17052429) (2021)
The research interest in sustainable and eco-friendly materials based on natural sources has increased dramatically due to their recyclability, biodegradability, compatibility, and nontoxic behavior. Nanocellulose contains chains of glucose residue and is an abundantly available green material. Recently, nanocellulose-based green composites are under extensive exploration and gained popularity among researchers owing to their lightweight, lost cost, low density, excellent mechanical and physical characteristics. These materials have also shown tremendous potential for applications in biomedical and numerous engineering fields. The mechanical properties of these materials play a vital role in effective utilization and their exploration for future applications. This review article comprehensively presents current developments, results, and findings in the arena of green and sustainable materials. Currently, the main problem is the large variability in their properties and qualities. Nanocellulose properties are influenced by various factors, including the fiber type, ecological conditions, manufacturing methods, and any alteration of the fiber surface. Finally, the review incorporates future challenges and opportunities in the field of nano cellulosic materials. Other Information Published in: Journal of Materials Research and Technology License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.jmrt.2021.07.128